ANALISIS KINERJA KEUANGAN PT GUDANG GARAM TBK MENGGUNAKAN RASIO KEUANGAN PERIODE 2022-2024 - Melsa Ulfie Wahyudianty; Bangbang Hardianto; Sundari Rifka Natasya; Gunardi Gunardi; Priatna Kesumah (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
The Indonesian tobacco industry is facing increasing pressure due to economic volatility and the policy of increasing Tobacco Excise Tax (CHT) during the 2022-2024 period. PT Gudang Garam Tbk, one of the largest cigarette companies in Indonesia, experienced a negative impact on its financial performance as a result of this situation. The objective is to assess the financial performance of PT Gudang Garam Tbk using financial ratios. The theoretical basis and literature review used include the concepts of financial performance, financial statements, and analysis of liquidity, solvency, and profitability ratios. This research was conducted using a quantitative and descriptive approach. Data mining methods were carried out through secondary data collection in the form of PT Gudang Garam Tbk's annual financial reports for the 2022-2024 period obtained from the Indonesia Stock Exchange website and the company. The results indicate that the company has a strong level of liquidity and solvency, reflected in a high current ratio and a decreasing debt ratio. However, the profit margin ratio, Return on Assets, and Return on Equity decreased drastically in 2024, indicating a decline in profitability performance. This study concludes that PT Gudang Garam Tbk is in a balanced financial condition in terms of liquidity and capital structure, but faces major challenges in maintaining profitability.